Implementing Inquiry-Based and Online Mentoring in a Social Entrepreneurship Project - Nicolaou, Anna (My University, 2022)
This paper presents the results of implementing an inquiry-based and online mentoring intervention in a project revolving around social entrepreneurship. The intervention was implemented in the context of an English for Specific Purposes (ESP) module at a higher institution and aimed at developing learners’ 21st century skills, such as team work, problem-solving and communication as well as social entrepreneurial competence. Thirty-three ESP students majoring in Business Management at a higher institution participated in the intervention which was implemented within an online mentoring platform. The analysis of both quantitative and qualitative data yielded interesting results pertaining to the students’ interaction and engagement activity on the mentoring platform, the learning gains, as well as their perceptions of the ways in which the online mentoring experience contributed towards the effective completion of their social entrepreneurship project. Emerging themes include the benefits of the intervention in building discipline-specific knowledge and social entrepreneurial competence, as well as in enhancing communication and team work skills. As for the challenges faced by the students during their online mentoring experience, these included difficulty in composing interesting and creative questions addressed to the mentors, lack of confidence in posting video questions on the platform, and delayed responses from the mentors.
Keywords: Inquiry-based learning; Online mentoring; Project-based learning